ФИЗИКО-ХИМИЧЕСКИЕ ПАРАМЕТРЫ ФОРМИРОВАНИЯ ИЗУМРУДНОЙ МИНЕРАЛИЗАЦИИ НА ПРИМЕРЕ МЕСТОРОЖДЕНИЙ УРАЛА - Мейксина Ю.Л.; Евдокимов М.Д. (My University, 2005)
Study of the Urals emerald deposits attracted the great attention since their discovery in 1831. Among their investigators, there arc known A. E. Fersman (1925-1940), A. I. Ginsburg (1955, 1959), E. Ya. Kievlenko (1980, 1982) e. a. The last decades were remarkable by elaboration of the pneumatolytic-hydrothcrmal genetic model of the emerald occurrences. It assumes that formation of the phlogopite mica rocks preceded the emerald mineralization (A. I. Sherstyuk, 1965; V. I. Zhernakov, 1980, 1993; μ. P. Popov, 1999; E. V. Gavrilenko, 2000, Y. L. Meiksina, 2003). The present paper displays data of physical-chemical analysis of mineral parageneses ob-served in the Urals Emerald mines. Diagrams within uBe and uCa2+ as coordinate axes represent associations of major and secondary minerals, such as beryl (emerald), chrysoberyl, phenakite, plagioclase, phlogopite, mar-garite, trcmolite. The block-diagrams of stability fields are constructed for the main minerals within coordinates of pH indices, activities of Be2+ and H4SiO4.
Keywords: 549.646.2:553.21